Dual role of φ29 DNA polymerase Lys529 in stabilisation of the DNA priming-terminus and the terminal protein-priming residue at the polymerisation site. - Alicia del Prado (Public Library of Science (PLoS), 2013)
Resolution of the crystallographic structure of φ29 DNA polymerase binary and ternary complexes showed that residue Lys529, located at the C-terminus of the palm subdomain, establishes contacts with the 3' terminal phosphodiester bond. In this paper, site-directed mutants at this Lys residue were used to analyse its functional importance for the synthetic activities of φ29 DNA polymerase, an enzyme that starts linear φ29 DNA replication using a terminal protein (TP) as primer. Our results show that single replacement of φ29 DNA polymerase residue Lys529 by Ala or Glu decreases the stabilisation of the primer-terminus at the polymerisation active site, impairing both the insertion of the incoming nucleotide when DNA and TP are used as primers and the translocation step required for the next incoming nucleotide incorporation. In addition, combination of the DNA polymerase mutants with a TP derivative at residue Glu233, neighbour to the priming residue Ser232, leads us to infer a direct contact between Lys529 and Glu233 for initiation of TP-DNA replication. Altogether, the results are compatible with a sequential binding of φ29 DNA polymerase residue Lys529 with TP and DNA during replication of TP-DNA.